Mendorong Organizational Citizenship Behavior Melalui Peran Supervisor Support di Hotel Danau Toba Internasional Medan - Orlana Devina Ariestha Zebua; Rianda Elvinawanty; Juni Santy Theresia Sihotang; Claura Noi Br Simangunsong; Mukhaira El Akmal (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Organizational Citizenship Behavior (OCB) is a crucial indicator for improving employee performance and service quality in the hospitality industry. However, the implementation of OCB is strongly influenced by the support provided by supervisors. Lake Toba International Hotel in Medan, as a star-rated hotel, faces challenges in enhancing employee motivation and commitment, particularly in engaging employees beyond their formal duties. This study aims to examine the relationship between Supervisor Support and OCB among hotel employees. A quantitative approach was employed using the Pearson Product Moment correlation technique, involving 105 employees as respondents. The analysis revealed a positive and significant relationship between Supervisor Support and OCB, with a correlation coefficient of 0.672 and significance of 0.000 (p < 0.05). This indicates that higher supervisor support is associated with higher employee OCB. Furthermore, the R Square value of 0.452 indicates that Supervisor Support contributes 45.2% to OCB, while the remaining 54.8% is influenced by other factors. These findings highlight the critical role of supervisors in creating a supportive work environment, including guidance, recognition, and emotional support, which directly encourage employees to engage in behaviors beyond their formal duties. In conclusion, enhancing supervisor support can be an effective strategy for Lake Toba International Hotel management to increase employee engagement, loyalty, and performance through OCB. This study offers practical implications for hotel management in designing leadership development programs and strengthening supervisor–employee relationships.